Montelukast as a Renal Protective Adjunct in Childhood Steroid-sensitive Nephrotic Syndrome: A Quasi-experimental Study: Prednisolone Alone Versus Combined With Montelukast in the Treatment of NS - Sadeghi Bojd, Simin; Shahraki Ghadimi, Zahra; Sheikhi, Vahid; Karimi, Fatemeh; Payandeh, Abolfazl (Journal of Pediatric Nephrology, 2026)
Background and Aim: Nephrotic syndrome (NS) is the most common glomerular disease in children in Iran, with high relapse rates and steroid-related complications. Montelukast, a leukotriene receptor antagonist, has shown potential as a steroid-sparing agent, but its renal protective effects remain debated. This study aimed to compare the efficacy of prednisolone monotherapy versus combined prednisolone-montelukast therapy in pediatric NS, focusing on renal function, metabolic parameters, and safety. Methods: A quasi-experimental study involving 66 children with NS was conducted at Ali Bin Abi Taleb Hospital, Iran (2022). Participants were divided into two groups: Group A (prednisolone+montelukast, n=33) and group B (prednisolone alone, n=33). Primary outcomes included time to remission and 6-month relapse rates. Secondary outcomes were serum albumin, urine protein-to-creatinine ratio (Upro/Cr), estimated glomerular filtration rate, and adverse events. Results: Both groups showed significant improvements in albumin, cholesterol, and proteinuria (P<0.001). However, group A demonstrated superior renal protection, with a significant reduction in serum creatinine (−0.08 mg/dL vs +0.11 mg/dL in group B, P=0.001). Subgroup analysis revealed enhanced creatinine improvement in children <6 years (P=0.02). No serious adverse events were reported, and safety profiles were comparable (gastrointestinal symptoms: 12.1% vs 9.1%, P=0.7). Conclusion: Adjunctive montelukast provides additional renal protection, particularly in younger children, without compromising metabolic efficacy or safety. These findings support its consideration in high-risk pediatric patients with NS, warranting further long-term studies.